Awareness of adverse drug reactions in third M.B.B.S students practicing self-medication - Burute, Shreyas R.; Burute, Ramchandra B.; Murthy, Mangala B.; Karande, Vitthal B.; Pore, Shraddha M.; Ramanand, Sunita J. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Students self-medicate but the extent of their knowledge regarding potential adverse drug reactions (ADRs) to drugs consumed by them is not known. This has many implications. This study has attempted to evaluate this knowledge in third MBBS students practicing self-medication. Methods: In this cross-sectional study, a self-designed, pretested questionnaire was presented to third MBBS students in a teaching hospital. Information sought:-Demographic data, self-medication drugs used within last one month, indication, duration, awareness and expected ADRs for the drugs consumed. Results were calculated as percentages. Results: 79 out of 87 third MBBS students present on the day of study were presented with questionnaire all attempted it; giving a response rate of 100%. Within the last one month 31 (39.24%) had self-medicated. There was no significant difference in self-medication between male and female students. Medication was used for adequate duration (93.87%) and for apparently correct indications (81.6%) by most students. Main group of drugs consumed were NSAIDs including antipyretics (42.59%), antibiotics (18.53%) and antihistaminics (16.66%). Fourteen (45.16%) students said they were aware of potential ADRs to the consumed drugs and 13 (43.93%) listed expected ADRs correctly .Although a wide range of drugs were consumed, the number of ADRs mentioned were few and its spectrum limited. 11 (35.48%) students mentioned only one ADR. No student mentioned more than two ADRs. Dyspepsia (56.25%) was most common ADR stated. Conclusions: Considering the wide range of drugs consumed, the numbers of ADRs mentioned were few and their spectrum limited indicating scope for improvement.